Intermittent fasting vs Ramadhan fasting / Sharifah Maimunah Syed Mud Puad, Mohd Faridz Ahmad and Muhammad Wafi A.Rahman - Syed Mud Puad, Sharifah Maimunah; Ahmad, Mohd Faridz; A.Rahman, Muhammad Wafi (UiTM Cawangan Negeri Sembilan Kampus Seremban, 2022)
Intermittent fasting (IF) is becoming more popular as a weight-loss strategy. Many manage to lose weight with this strategy when practicing significant calorie reduction with restricted eating periods while fasting. But, is intermittent fasting the same as Ramadhan fasting? The main similarity is the practice of abstinence from food and drink. However, the difference is in the purpose and goal of the fasting: one is for religious and spiritual reasons, while the other is to lose weight.